CAPITAL STRUCTURE DETERMINANTS OF PLANTATION SUB-SECTOR COMPANIES IN INDONESIA STOCK EXCHANGE PERIOD 2014 – 2018 - Wildan Mujaddid, Septian; Bambang Santoso Marsoem (Dinasti International Journal of Economics, Finance & Accounting, 2020)
The purpose of this study is to analyze the factors that influence the Debt to Asset Ratio which is a proxy of Capital Structure as the dependent variable. The independent variables studied as determinants of Capital Structure (DAR) include Size (SIZE), Profitability (ROA), Asset Structure (SA), and Corporate Liquidity (CR) using regression model. The population in this study are plantation sub-sector companies listed on the Indonesia Stock Exchange for the period 2014 - 2018. The findings suggest that ROA negatively significant affect DAR, while SA positively significant affect DAR. On the other hand, both SIZE & CR have no significant relationship with DAR